2017
DOI: 10.24912/ja.v19i1.119
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI DAN MOTIVASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur di Jakarta dan Tangerang)

Abstract: Abstract:The purpose of this research is to analyst the influence of participation in composing budget toward managerial performance, whether through organization commitment and motivation as moderating variable. The inconsistency situations between results of the prior research, about the influence of budget participation on managerial performance become a motivation of this study. Data used in this study is obtained from ideas or perceptions of managers who filled and gave the questionnaires back to the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 4 publications
2
9
1
4
Order By: Relevance
“…Therefore, it can be concluded that the variable budget participation has a positive effect on managerial performance. The results of this study are in line with the results of research conducted by Murwaningsari (2008), Noor and Othman (2012), Saraswati and Aisyah (2015), Savitri et al (2015), Gunawan and Santioso, (2015), Hariyanti et al (2015), and Ernis et al (2017) which show the positive influence of budget participation on managerial performance directly. Budget participation can increase understanding, effort, and motivation of managers in achieving budget targets and can improve the quality of the budget which will lead to enhance managerial performance of managers.…”
Section: Hypothesis Test Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, it can be concluded that the variable budget participation has a positive effect on managerial performance. The results of this study are in line with the results of research conducted by Murwaningsari (2008), Noor and Othman (2012), Saraswati and Aisyah (2015), Savitri et al (2015), Gunawan and Santioso, (2015), Hariyanti et al (2015), and Ernis et al (2017) which show the positive influence of budget participation on managerial performance directly. Budget participation can increase understanding, effort, and motivation of managers in achieving budget targets and can improve the quality of the budget which will lead to enhance managerial performance of managers.…”
Section: Hypothesis Test Resultssupporting
confidence: 91%
“…Several previous studies have been proved organizational commitment influences the relationship between budget participation and managerial performance. Sumarno (2005), Murwaningsari (2008), Nuraini and Rosyati (2012), Gunawan and Santioso (2015), and Arifuddin et al (2017) on their research found a positive relationship of organizational commitment in strengthening the relationship of budgetary participation with managerial performance. H2: The higher the level of organizational commitment, the more positive budget participation influences managerial performance.…”
Section: The Effect Of Organizational Commitment On the Relationship Between Budget Participation And Managerial Performancementioning
confidence: 95%
See 3 more Smart Citations